Recognizing Dynamic Fields in Network Traffic with a Manually Assisted Solution - Jarko Papalitsas; Jani Tammi; Sampsa Rauti; Ville Leppänen (My University, 2022)
Payloads of packets transmitted over network contain dynamic fields that represent many kinds of real world objects. In many different applications, there is a need to recognize and sometimes replace these fields. In this paper, we present a manually assisted solution for searching and annotating dynamic fields in message payloads, specifically focusing on web environment. Our tool provides a simple and intuitive graphical user interface for annotating dynamic fields.
Trends and Advances in Information Systems and Technologies Volume 2